Coronary anatomy characteristics in patients with isolated right bundle branch block versus subjects with normal surface electrocardiogram - Pakbaz, Marziyeh (2013)
INTRODUCTION AND OBJECTIVE: Isolated right bundle branch block is a common finding in the general population. It may be associated with variations in detailed coronary anatomy characteristics. The aim of this study was to investigate the coronary anatomy in patients with isolated right bundle branch block and to compare that with normal individuals. METHOD: In this case–control study we investigated the coronary anatomy by reviewing angiographic films in two groups of normal coronary artery patients: patients with right bundle branch block (RBBB) (n = 92) and those with normal electrocardiograms (n = 184). RESULTS: There was no significant difference between the two groups in terms of diminutive left anterior descending artery, dominancy, number of obtuse marginal artery, diagonal, acute marginal artery, the position of the first septal versus diagonal branch, presence of ramus artery, and size of left main artery. The number of septal branches was higher in the case group (p-value <0.001). Origination of the atrioventricular node artery from the right circulatory system was more common in both groups but cases showed more tendency to follow this pattern (p-value = 0.021). The frequency of the normal conus branch was higher in the cases versus controls (p-value = 0.009). CONCLUSIONS: Coronary anatomy characteristics are somewhat different in subjects with RBBB compared to normal individuals.